2020
DOI: 10.3390/ijerph17207421
|View full text |Cite
|
Sign up to set email alerts
|

Public Spaces as Knowledgescapes: Understanding the Relationship between the Built Environment and Creative Encounters at Dutch University Campuses and Science Parks

Abstract: The success of university campuses depends on the interrelations between creative encounters and the built environment, conceptualised here as spatial affordances for creativity. Such an interface plays a fundamental role in interactions for knowledge sharing and the exchange of ideas on campus. Due to campus public spaces generally being considered as the leftovers between buildings and classrooms, undermanaged, and overlooked, little is known about the extent to which this built environment enables or inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…The study by Soares et al [ 22 ] combined location data by means of online maps and questionnaires to collect data on people’s momentary perceptions, specifically creative encounters, with urban public spaces at university campuses, which is called Volunteered Geographic Information (VGI). In addition, secondary objective data of the built-up environment (e.g., Openstreet Map) was used.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study by Soares et al [ 22 ] combined location data by means of online maps and questionnaires to collect data on people’s momentary perceptions, specifically creative encounters, with urban public spaces at university campuses, which is called Volunteered Geographic Information (VGI). In addition, secondary objective data of the built-up environment (e.g., Openstreet Map) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Studies from Resch et al [ 20 ], Pykett et al [ 29 ], Ristea et al [ 21 ] and Soares et al [ 22 ] showed that combining different data sources (sensors and surveys) and linking them to space via geospatial approaches enhanced citizen engagement in field lab settings and offers potentials for evidence-based planning.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations